A detailed chemical kinetic model of high-temperature ethylene glycol gasification - Hafner, Simon; Rashidi, Arash; Baldea, Georgiana; Riedel, Uwe (Combustion theory and modelling, 2011)
In recent experimental investigations, ethylene glycol is used as a model substance for biomass-based pyrolysis oil in an entrained flow gasifier. In order to gain a deeper insight into process sequences and to conduct parametric analysis, this study describes the development and validation of a detailed chemical kinetic model of high-temperature ethylene glycol gasification.